A study on R&D expenditure and corporate value of Chinese high-tech industry - Guan-Chih Chen; Hexuan Li; Shuling Tsao (Financial Studies, 2019)
This paper examines the impact of research and development (R&D) expenditure, R&D capitalized expenditure and expensed expenditure on the corporate value. Through the exposition of R&D expenditure affect relevance of corporate value after the Chinese New Accounting Standards, it can be found that R&D expenditure information has a positive effect on share price. The disclosure of information on R&D expenditure has a positive relevance to corporate value means that the disclosure of R&D expenditure information can improve the value relevance of accounting information. Investors give positive value to the R&D capitalized and expensed expenditure, but R&D capitalized expenditure has a greater effect on investors than R&D expensed expenditure. At the same time, the normative degree of R&D expenditure disclosure has a significant positive effect on the stock price, which shows that the disclosure of R&D expenditure information can improve the value relevance of accounting information.
Keywords: C33; G30; M41; O14; 330; Chinese High-tech industry; R&D capitalized expenditure; corporate value